2019
DOI: 10.15537/smj.2019.3.23940
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography pulmonary angiography using high-pitch dual-source scanner technology

Abstract: Objectives: To compare use of ultra-fast high-pitch dual-source free-breathing computed tomography pulmonary angiogram (CTPA) with conventional standard-pitch single-source breath-hold CTPA. Methods: This retrospective comparative study was conducted in Radiology Department at King Fahad Military Medical Complex Dhahran, Saudi Arabia from July 2016 to December 2017. Patients (N=130) were divided into 2 groups, each having 65 consecutive patients; Group-1 (single-source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Studies comparing the high-pitch and routine scanning for pulmonary embolism CT have shown improved image quality, decreased artifacts, and decreased radiation dose with high-pitch imaging [6,7]. This improvement in image quality is associated with better delineation of cardiovascular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the high-pitch and routine scanning for pulmonary embolism CT have shown improved image quality, decreased artifacts, and decreased radiation dose with high-pitch imaging [6,7]. This improvement in image quality is associated with better delineation of cardiovascular structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be significant discordance (25%) among radiologists when assessing small subsegmental contrast filling defects. [37] Our results are adequately validated since all CTPA studies were reported by a single experienced radiologist. Moreover, we excluded all poor quality CTPA cases from our study.…”
Section: Discussionmentioning
confidence: 55%
“…However, there may be significant discordance (25%) among radiologists when assessing small subsegmental contrast filling defects. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is capable of directly visualizing emboli and may even provide an alternate diagnosis. 18 There are concerns over increased availability of CTPA leading to its overuse in diagnostic workup of patients having cardio-respiratory symptoms. 19 However, in case of positive D-dimers and high or a "likely" clinical probability, CT pulmonary angiography is now the recommended imaging technique.…”
Section: Discussionmentioning
confidence: 99%